Influence of strength inhomogeneity on transboundary expansion characteristics of hydraulically fractured fractures in coal seams - Dongbin Huang; Xiangtao Kang; Zuhao Xu; Chao Ren; Yongyan Long; Ping Cao (Scientific Reports)
Abstract Coal, a vital strategic resource, facilitates industrial development and socio-economic progress. Ensuring the high-quality development of the coal industry is crucial for national energy security and safety. Coal and gas outbursts are frequent hazards in coal mining processes. This research delves into the impact of heterogeneous coal seam strength on hydraulic fracturing propagation, utilizing both physical experimentation and the ABAQUS finite element approach. Experimental findings reveal distinct variations in water injection pressure profiles and fracturing fluid distribution patterns within coal seams of varying strengths, in contrast to those exhibiting uniform strength. When fractures propagate from a weaker to stronger coal seam region, a notable increase in pressure build-up effect is observed, leading to higher water injection pressure, wider fracture widths, augmented coal body displacement, and an elevated rate of rigidity reduction. In this study, the physical test results and numerical simulation results are verified with each other. After fractures propagate across the interface, zone with higher coal seam strength experience decreased fracture width, lower coal body displacement, and slower rates of rigidity decline compared to weaker seam zone. When fractures propagate from high to low coal seam areas, the fracture experiences instantaneous cross-boundary extension, resulting in a decrease in pore pressure, increased coal body displacement, and an elevated rate of rigidity decline.